Long-term evaluation of postmastectomy breast reconstruction with the pedicled transverse rectus abdominis musculocutaneous flap. Issue 5 (October 2013) - Christensen, Bekka O.; Overgaard, Jens; Kettner, Laura O.; Damsgaard, Tine E.
Abstract The transverse rectus abdominis musculocutaneus (TRAM) flap is ideal for unilateral breast reconstruction. It can produce a breast with a lasting natural look, soft feeling, and good resemblance to the opposite breast. The aim was to evaluate long-term results of the TRAM flap reconstruction in an homogenous study population and to examine the impact on abdominal competence, appearance, and function relative to patient satisfaction. The study included 123 women from the cohort of patients undergoing a postmastectomy breast reconstruction in the period from 1992–2005. Data was collected from patient charts, a study-specific questionnaire, and a clinical follow-up visit. The response to the questionnaire was 81% (100/123), and 78 of them participated in a clinical follow-up visit. Eighty-four per cent were satisfied with the overall results of their breast reconstruction, and the majority of the women were pleased with the overall appearance of their abdomen. A significant correlation existed between satisfaction with the abdominal appearance and donor site complications (p = 0.01). No association was determined between complications in the breast area and smoking. A BMI above 25 increased the risk of complications. Radiation therapy (RT) significantly increased the risk of severe complications (p = 0.04) and of an inferior aesthetic result (p = 0.03). In conclusion, after a median of 6 years, women reconstructed with a TRAM flap were pleased with the overall result, with the appearance and strength of their abdomen including the umbilicus. Breast reconstruction with the pedicled TRAM flap results in lasting good results and pleased patients.